Environmental R&D - Michael Hoel (University of Oslo, Department of Economics, 2010)
The topic of this note is issues related to R&D expenditures leading to improved technologies for reducing environmentally harmful emissions. The focus is on he following questions: Will a market economy where environmental policies are restricted to taxes or quotas give the socially efficient outcome for such R&D? Does the answer to this question depend on whether one uses taxes or quotas to regulate emissions? Are market failures associated with environmental innovations different than for innovations elsewhere in the economy?
Keywords: O3; Q5; Q55; 330; Environmental policy; R&D; endogenous technological development; Umwelttechnik; Forschung; Technischer Fortschritt; Marktversagen; Umweltpolitik; Ökosteuer; Quotenregulierung; Theorie